Analisis Sentimen Pengguna Terhadap Aplikasi Bing Chat di Google Play Store dengan Metode Naïve Bayes - Dimas Cahyo Ramadhan; Faldy Irwiensyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The development of technology that occurs at this time is increasingly rapid, so it can be said to be an era of technological revolution where at this time almost all activities in society have used technology. One of the technologies that emerged in the current era of technological development is artificial intelligence(AI) technology. Artificial intelligence refers to the ability of computers to learn, adapt, and make decisions based on data. Currently, there are many artificial intelligence technologies in the form of applications that can be easily downloaded for free on the Google Play Store, one of which is the application resulting from the partnership between Microsoft and OpenAI, namely Bing Chat. The presence of Bing Chat as one of the artificial intelligence applications on the Google Play Store raises various user reviews while using the artificial intelligence technology. Based on this, a method is needed to analyze the various reviews on the Bing Chat application. This research aims to analyze user sentiment reviews of the Bing Chat application on the Google Play Store with the Naïve Bayes method. A total of 2000 user sentiment review data for the Bing Chat application on the Google Play Store in the January to February 2024 timeframe were collected using the web scrapping method. After going through the analysis process, 1877 sentiment data were obtained with 1653 positive sentiment data and 224 negative sentiment data. The evaluation results of this research on the sentiment of the Bing Chat application on the Google Play Store with the Naïve Bayes algorithm method get the results of the accuracy value of 67.16%, precision 93.53%, and recall 67.39%.